2017
DOI: 10.1021/acs.jpcc.6b09919
|View full text |Cite
|
Sign up to set email alerts
|

Isomerization in Gold Clusters upon O2 Adsorption

Abstract: A systematic investigation is performed on structural transformations in small neutral gold clusters (Au3–Au12) induced by O2 adsorption, with the use of the fully automated reaction path search techniques, i.e., anharmonic downward distortion following (ADDF) and artificial force induced reaction (AFIR) methods, implemented in the global reaction route mapping (GRRM) program. For each size of Au cluster, the most stable structure, low-energy isomers, and a network of isomerization pathways are determined. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 70 publications
1
32
0
2
Order By: Relevance
“…Haruta et al first observed the remarkable catalytic activity of gold nanoparticles, notably toward oxidation reactions involving molecular oxygen. This has been extended to few‐atom Au m ( m ≲ 20) clusters in gas‐phase studies, illuminating their atom‐to‐atom size‐dependent affinity for oxygen adsorption and dissociation, relevant reaction pathways, and the dependence of the reactivity on the initial charge state of the cluster …”
Section: Doping Efficiency For (O2/)aum/g With M = 3mentioning
confidence: 99%
See 2 more Smart Citations
“…Haruta et al first observed the remarkable catalytic activity of gold nanoparticles, notably toward oxidation reactions involving molecular oxygen. This has been extended to few‐atom Au m ( m ≲ 20) clusters in gas‐phase studies, illuminating their atom‐to‐atom size‐dependent affinity for oxygen adsorption and dissociation, relevant reaction pathways, and the dependence of the reactivity on the initial charge state of the cluster …”
Section: Doping Efficiency For (O2/)aum/g With M = 3mentioning
confidence: 99%
“…For free (neutral) Au 3 clusters, one has observed two isomers which are close in energy (energy difference on the order of 20 meV) . One isomer has a triangular geometry, while the other isomer portrays a more linear shape.…”
Section: Doping Efficiency For (O2/)aum/g With M = 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Global optimization is the standard procedure for exploring the Potential Energy Surface (PES) and identifying the most stable structure of catalytic clusters . For gas phase and surface supported clusters, many different global optimization approaches have been extensively studied, including genetic algorithm, Basin Hopping (BH), and neural network fitting After the shape of catalytic clusters is identified by global optimization, the global minimum structure and possibly some other low‐energy isomers can be selected as reference states, for studying active sites for various reactants and corresponding reaction pathways . However, despite the relatively low computational cost, this scheme may not be reliable if the low‐energy bare‐cluster isomers do not appear to be the most active ones, or if a big shape change occurs upon the adsorption of reactants.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] For gas phase and surface supported clusters, many different global optimization approaches have been extensively studied, including genetic algorithm, [14,15] Basin Hopping (BH), [16,17] and neural network fitting [13,18,19] After the shape of catalytic clusters is identified by global optimization, the global minimum structure and possibly some other low-energy isomers can be selected as reference states, for studying active sites for various reactants and corresponding reaction pathways. [7,[20][21][22] However, despite the relatively low computational cost, this scheme may not be reliable if the low-energy bare-cluster isomers do not appear to be the most active ones, or if a big shape change occurs upon the adsorption of reactants. In particular, this will be the case when the catalytic cluster itself is highly fluxional, or if adsorbates affect the cluster shape.…”
Section: Introductionmentioning
confidence: 99%